SISTEM KONTROL DAN MONITORING ALIRAN DAYA LISTRIK PADA JARINGAN DISTRIBUSI TEGANGAN RENDAH MENGGUNAKAN MIKROKONTROLER BERBASIS IOT - Slamet Hariyadi; Hartono Hartono; Rifdian I.S.; Setiyo Setiyo; Siti Julaihah (Politeknik Penerbangan Surabaya, 2023)
To meet the needs of small or large scale electricity supply, the use of electrical energy generally uses 1 phase electricity and 3 phase electricity which is used to operate electrical equipment. To be able to find out the voltage, current, and electrical power of the low-voltage distribution network, manual checks are carried out on each R, S, T phase which is on the low-voltage distribution panel. When a 3-phase power failure occurs, it is often difficult to identify which phase is failingSo that in this case it is considered less efficient, for this research is expected to overcome the problems that have been identified. So a tool is made that can monitor failures in the R, S, and T phases which functions as safety when a failure occurs and can display a notification in which phase a failure occurs.In this study, the PZEM-004T sensor, Wemos D1 mini-module, and Android Studio are used which can allow for remote monitoring using electronic devices that have installed applications that have been created. when an error occurs, the